Nutrient Enrichment of Cow Manure-Based Organic Fertilizer at Subak Mertasari, Jembrana - Yohanes Parlindungan Situmeang; Ida Bagus Komang Mahardika; Evik Andiharta; Rahma Ciptaningrum; Yolanda Ezra Angelia Situmeang (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Cow manure waste at Subak Mertasari, Jembrana, Bali, was largely unprocessed and applied raw to agricultural fields, causing slow nutrient release and environmental contamination. This community service program responded to that problem by introducing a nutrient-enrichment method for cow manure-based organic compost, using biochar, effective microorganisms (EM4), molasses, agricultural lime (dolomite), and NPK fertilizer as enrichment agents. Twenty subak members took part across five implementation stages: socialization, technical training, compost production, quality monitoring, and business sustainability. Biomass waste was first converted to porous biochar through pyrolysis, then co-composted with inoculated cow manure over roughly 30 days. The resulting fertilizer met SNI 19-7030-2004 criteria: dark brown to black, crumbly, moisture below 20%, and free of offensive odor. Biochar addition raised soil pH and cation exchange capacity (CEC) while locking carbon in a stable form that limits greenhouse gas release. On the socio-economic side, farmers gained the skills to produce fertilizer independently, and a cooperative-based business unit was established for commercial distribution. These results show that integrated compost enrichment is a practical and scalable approach to sustainable agriculture in Bali. Contribution to Sustainable Development Goals (SDGs):SDG   2: Zero HungerSDG 12: Responsible Consumption and ProductionSDG 13: Climate ActionSDG 15: Life on Land